Design and Synthesis of Aromatics through [2+2+2] Cyclotrimerization - Kotha, Sambasivarao; Lahiri, Kakali; Sreevani, Gaddamedi (Synlett, 2018)
The [2+2+2] cycloaddition reaction is a useful tool to realize unusual chemical transformations which are not achievable by traditional methods. Here, we report our work during the past two decades that involve utilization of transition-metal complexes in a [2+2+2] cyclotrimerization reaction. Several key “building blocks” were assembled by a [2+2+2] cycloaddition approach and they have been further expanded by other synthetic transformations to design unusual amino acids and peptides, diphenylalkanes, bis- and trisaryl benzene derivatives, annulated benzocycloalkanes, spirocycles, and spirooxindole derivatives. Furthermore, we have also discussed about alkyne surrogates, environmentally friendly, and stereoselective [2+2+2] cycloaddition reactions. Application of the [2+2+2] cycloaddition reaction in total synthesis is also covered. In this review we also included others work to give a balanced view of the recent developments in the area of [2+2+2] cycloaddition.1 Introduction2 Unusual Amino Acids and Peptides3 Heteroanalogues of Indane4 Diphenylalkane Derivatives5 Multi-Armed Aryl Benzene Derivatives6 Annulated Benzocycloalkanes7 Spirocycles8 Selectivity in [2+2+2] Cycloaddition of Alkynes9 [2+2+2] Cycloaddition Reactions under Environmentally Friendly Conditions10 Alkyne Surrogates11 Domino Reactions involving a [2+2+2] Cycloaddition12 Biologically Important Targets/Total Synthesis13 Conclusions
Keywords: [2+2+2] cyclotrimerization; Diels–Alder; sultine; amino acids and peptides; spirocycles; Wilkinson’s catalyst; Vollhardt’s catalyst; alkyne surrogates